'We Are Fire Clan': Groups, Names and Identity in Papua New Guinea. Issue 1 (15th February 2018) - Dwyer, Peter D.; Minnegal, Monica
Abstract : This paper draws on two case studies concerning Kubo and Febi people of Western Province, Papua New Guinea, to reveal, first, ways in which people present themselves to the state as groups that qualify as legitimate beneficiaries of financial benefits expected to flow from extraction of natural gas on or near their land and, second, simultaneously present themselves to their immediate neighbours in ways intended to either lay claim to particular areas of land or offset possible challenges to their asserted rights to land. To achieve these ends, people strategically employ names to variously connote or denote particular assemblages of people.